2019
DOI: 10.1021/acsami.9b06545
|View full text |Cite
|
Sign up to set email alerts
|

[MoS4]2–-Intercalated NiCo-Layered Double Hydroxide Nanospikes: An Efficiently Synergized Material for Urine To Direct H2 Generation

Abstract: Substituting the energy-uphill water oxidation half-cell with readily oxidizable urea-rich urine, a ground-breaking bridge is constructed, combining the energy-efficient hydrogen generation and environmental protection. Hence, designing a robust multifunctional electrocatalyst is desirable for widespread implementation of this waste to fuel technology. In this context, here, we report a simple tuning of the electrocatalytically favorable characteristics of NiCo-layered double hydroxide by introducing [MoS4]2– … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 54 publications
(146 reference statements)
0
9
0
Order By: Relevance
“…Ni-based LDHs have been reported to display superior urea oxidation activity than noble metals (Pt, Pt-Ir, Rh) in alkaline media. [114][115][116][117][118][119][120][121][122][123][124][125][126] Moreover, the compositional tunability for both laminate cation and interlayer anion of LDHs can be further exploited to improve their urea oxidation performance. It has been reported that the doping of Co cations optimized the electroconductivity and regulated the electronic structure of NiFeCo-LDH, leading to a highly enhanced urea oxidation performance with lower onset potential (0.28 V vs. SCE to reach 10 mA cm -2 ) than NiFe-LDH (0.38 V) in 1 M KOH with 0.33 M urea.…”
Section:  Hydrogen Production Coupled With Ehco Based On Ldhsmentioning
confidence: 99%
“…Ni-based LDHs have been reported to display superior urea oxidation activity than noble metals (Pt, Pt-Ir, Rh) in alkaline media. [114][115][116][117][118][119][120][121][122][123][124][125][126] Moreover, the compositional tunability for both laminate cation and interlayer anion of LDHs can be further exploited to improve their urea oxidation performance. It has been reported that the doping of Co cations optimized the electroconductivity and regulated the electronic structure of NiFeCo-LDH, leading to a highly enhanced urea oxidation performance with lower onset potential (0.28 V vs. SCE to reach 10 mA cm -2 ) than NiFe-LDH (0.38 V) in 1 M KOH with 0.33 M urea.…”
Section:  Hydrogen Production Coupled With Ehco Based On Ldhsmentioning
confidence: 99%
“…[6][7][8] Nickel (Ni) and its derivatives are the widely reported as "efficient" catalysts for UOR in alkaline. [9][10][11][12][13][14][15][16][17][18][19][20][21] Because of the co-effect of alkaline environment and oxidation potential, the surface Ni component on these Ni-based materials will evolve into Ni oxyhydroxide (NiOOH) via a self-oxidation. [22][23][24][25][26][27] These generated NiOOH serve as active sites to react with urea and degrade it through spontaneous redox.…”
mentioning
confidence: 99%
“…As can be seen in Figure a–c, compared with LDHs, the Mg 2p, Al 2p, and Zr 3d spectra of P-LDHs and GEP-LDHs all shifted toward a higher binding energy, but the spin-energy separation of Zr 3d unchanged. This can be interpreted as the replacement of NO 3 – in the interlayer by P and GEP with a lower charge density. , The zeta potential of LDHs, P-LDHs, and GEP-LDHs is 14.8, −23.4, −17.3, 3.8, and 6.1 mV, respectively (Figure d). The zeta potential of P-LDHs and GEP-LDHs is between that of LDHs and P, and LDHs and GEP, respectively, indicating the existence of electrostatic interaction between LDHs and P and GEP. , Moreover, the specific surface area of P-LDHs and GEP-LDHs increases from 113.73 to 146.53 and 136.74 m 2 ·g –1 , and the pore size increases from 8.99 to 25.17 and 21.19 nm, respectively (Figure e,f and Table ).…”
Section: Resultsmentioning
confidence: 99%